Impact of near-infrared fluorescence imaging with indocyanine green on the surgical treatment of pulmonary masses in dogs - Sakurai, Naoki; Ishigaki, Kumiko; Terai, Kazuyuki; Heishima, Tatsuya; Okada, Kazuki; Yoshida, Orie; Kagawa, Yumiko; Asano, Kazushi (Frontiers in Veterinary Science, 2023)
Objectives: To investigate the intraoperative identification and complete resection of pulmonary masses, and to evaluate lymph node metastasis of pulmonary malignant tumors in dogs using indocyanine green (ICG) fluorescence imaging. Methods: Forty dogs with pulmonary masses were included, all of which underwent surgical treatment. ICG fluorescence imaging was performed on pulmonary masses before lobectomy and the resection margins after lobectomy. In addition, ICG fluorescence of the excised masses and lymph nodes was evaluated in the shaded box. The fluorescence findings were compared with the histopathological diagnosis. Results: Of 44 nodules resected from 40 dogs, 32 nodules were histopathologically diagnosed as lung adenocarcinoma, five were histiocytic sarcoma, three were undifferentiated sarcoma, two were malignant epithelial tumor metastases, one was carcinosarcoma, and one was a non-neoplastic lesion. Fluorescence was observed in all nodules. In addition to the main lesion, other fluorescent nodules were found in four dogs. Regarding the diagnostic accuracy of complete resection based on ICG fluorescence, the sensitivity was 67.7% and the specificity was 60.0%. The sensitivity and specificity of ICG fluorescence for the diagnosis of lymph node metastasis were 100% and 75.0%, respectively. Conclusions: ICG fluorescence imaging might be a useful intraoperative diagnostic method to identify the location of tumors and lymph node metastasis, but not to evaluate complete tumor resection, in dogs with pulmonary malignant tumors.